Advancing The Green Transition on Technical Vocational Education and Training in Davao Del Norte - Francisco, John Mark; Jasmin Neri (Journal of Technical Education and Training, 2026)
This study explores the green transition within the Technical and Vocational Education and Training (TVET) system in Davao del Norte, Philippines, aiming to support a sustainable economy. We utilized the British Council’s Greening TVET Systems Self-Assessment Tool to assess seven key areas of green TVET: policy coherence, labor market intelligence, employer engagement, curriculum assessment, learner support, institutional strengthening, and financing. Data were collected from TVET administrators and green TVET focal persons from accredited training institutions, and we analyzed the information using descriptive statistics and the Friedman test. The findings revealed that the TVET sector in Davao del Norte shows moderate to high readiness to pursue green initiatives. Notably, employer engagement scored the highest, indicating strong collaboration from industry partners in areas such as curriculum development, governance, and work-based learning opportunities. Other areas like curriculum assessment and learner support also demonstrated promising progress. However, financing emerged as a significant challenge, highlighting insufficient resources for institutional transformation and green skills development. Despite these issues, the study concludes that Davao del Norte has a solid foundation for implementing green TVET. To fully support the transition to a sustainable economy, it is crucial to improve collaboration among institutions, develop sustainable financing strategies, enhance curricula, and build workforce capabilities. These insights contribute to the growing conversation on sustainable technical education and can serve as a valuable resource for policymakers and researchers interested in advancing green TVET systems in the Philippines.